Cellular disturbance and thermal stress response in mussels exposed to synthetic and natural microfibers - Pittura, Lucia; Nardi, Alessandro; Cocca, Mariacristina; De Falco, Francesca; d’Errico, Giuseppe; Mazzoli, Carola; Mongera, Federica; Benedetti, Maura; Gorbi, Stefania; Avella, Maurizio; Regoli, Francesco (Frontiers in Marine Science, 2022)
Textile microfibers (MFs) have natural (e.g. cotton, wool and silk) or synthetic origin (e.g. polyester and polyamide), and are increasingly documented in the marine environment. Knowledge on their biological effects in marine organisms is still limited, and virtually unexplored is their capability to modulate the responsiveness toward other stressors, including those of emerging relevance under global changes scenario. With such background, the aims of this study were to i) determine the ingestion and biological effects of MFs, discriminating between synthetic and natural ones, and ii) elucidate the possibility that MFs alter the responsiveness toward additional stressors occurring at a later stage, after exposure. Adult mussels Mytilus galloprovincialis were exposed for 14 days to a high but still environmentally realistic concentration of 50 MFs L-1 of either polyester (618 ± 367 µm length, 13 ± 1 µm diameter), polyamide (566 ± 500 µm length, 11 ± 1 µm in diameter) or cotton (412 ± 342 µm length, 16 ± 4 µm diameter). After the exposure, mussels were left for 7 days to recover at control temperature (23°C) or exposed to a heatwave condition (27°C). At the end of each phase (exposure – recovery – heat stress), MFs ingestion-elimination was evaluated, along with a wide panel of biological responses, including neuro-immune and antioxidant systems alterations, lipid metabolism and onset of cellular damages. Results were elaborated through a Weight of Evidence approach to provide synthetic hazard indices based on both the magnitude and toxicological relevance of observed variations. Beside limited differences in retention and elimination of MFs, biological analyses highlighted disturbance of the immune system and demand of protection toward oxidative insult, particularly evident in mussels exposed to synthetic-MFs. Carry-over effects were observed after 7 days of recovery: organisms that had been previously exposed to MFs showed a higher susceptibility of the neuroendocrine-immune system and lipid metabolism to thermal stress compared to un-exposed mussels. Overall, this study provided evidence of direct cellular effects of MFs, emphasizing differences between synthetic and natural ones, and highlighted their capability to modulate organisms’ susceptibility toward additional stressors, as those predicted for future changes in marine ecosystems.